2012
DOI: 10.5194/acp-12-2025-2012
|View full text |Cite
|
Sign up to set email alerts
|

Five-year record of atmospheric precipitation chemistry in urban Beijing, China

Abstract: Abstract. To investigate the chemical characteristics of precipitation in the polluted urban atmosphere in Beijing and possible mechanisms influencing their variations, a total of 131 event-based precipitation samples were collected from March 2001 to August 2005. The concentrations of major ions in the samples were analyzed by using ion chromatography. Intermediate pH (6.1-7.3) was recorded in approximately two-thirds of the precipitation samples and acidic pH (4.2-5.6) in only 16 % of the samples. However, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 41 publications
(39 reference statements)
5
21
0
Order By: Relevance
“…The increasing long heating period in winter, potential source of abundant sulfur emissions, might not be significantly balanced by NO x emissions essentially from regional mobile traffic. Over Dalian, the yearly ratio was 2.35 with high concentrations of both nssSO 4 2-and NO 3 -in winter, which is similar with that in Beijing with the value of 2.7 based on the five-year measurements reported by Yang et al (2012). This reflects the strong impact of local NO x emissions over Dalian where the mobile traffic is actually much more intense than that in Dandong.…”
Section: Acidification Process and Neutralization Effectsupporting
confidence: 73%
See 2 more Smart Citations
“…The increasing long heating period in winter, potential source of abundant sulfur emissions, might not be significantly balanced by NO x emissions essentially from regional mobile traffic. Over Dalian, the yearly ratio was 2.35 with high concentrations of both nssSO 4 2-and NO 3 -in winter, which is similar with that in Beijing with the value of 2.7 based on the five-year measurements reported by Yang et al (2012). This reflects the strong impact of local NO x emissions over Dalian where the mobile traffic is actually much more intense than that in Dandong.…”
Section: Acidification Process and Neutralization Effectsupporting
confidence: 73%
“…In comparison with Dandong, the acid rain was obviously less pronounced in Dalian city with relatively higher yearly pH vwa at HJS, LS (4.5) and GJZ (5.15). However, the acid rain in both cities seemed to be at the similar levels as those observed in Southwestern China (pH are in the range of 4.1-4.6) and Yangzi River (pH vwa 4.5) by (Aas et al, 2007) and (Huang et al, 2008), and more critical than the acidification process observed in Beijing (5 years rainfall records with pH vwa = 6.2) reported by Yang et al (2012).…”
Section: Analysis Of Precipitation Acidity Over Dalian and Dandongmentioning
confidence: 80%
See 1 more Smart Citation
“…Under the current national monitoring networks, only general urban air quality parameters and rainwater pH are measured, whereas little effort has been invested in determining the chemistry of the pollutants (Tang et al, 2010). Rapid advances have been made in recent years in the investigation of the chemical constituents responsible for the variations in precipitation pH (Huang et al, 2008;Sun et al, 2010;Tsai et al, 2011;Wai et al, 2005;Yang et al, 2012a), but most studies have been limited to a single site/year. Acid deposition can occur via the dry deposition of gases and particles and by wet deposition from rain, snow, clouds and fog (Flechard et al, 2011).…”
Section: Y P Pan Et Al: Wet and Dry Deposition Of Sulfur In Northementioning
confidence: 99%
“…About 10 years ago, atmospheric deposition studies had mainly focused on the acid rain causing ions (NO − 3 and SO 2− 4 ), due to the great harm caused by acid deposition [12,13]. With increasing human health concerns and the improvement of technology for detecting TMs, researchers have begun to pay attention to atmospheric TM deposition.…”
Section: Introductionmentioning
confidence: 99%